Optimization of inulin extraction from Inula helenium L. using response surface methodology followed by its MALDI-TOF and TLC-FLD based characterization - Mahdi Moridi Farimani; Elham Ahmadi; Hassan Rezadoost (Institue of Medicinal Plants, ACECR, 2022)
Background: Inulin, a prebiotic, is a mixture of linear chains β-2,1 fructans with a degree of polymerization (DP) of 2 to 60. Different DPs have various applications in the cosmetics, pharmaceutical, and food industries. Objective: This study aims to find the best method for DP determination. Methods: RSM was applied to optimize the extraction of inulin from Inula helenium. Four factors, including time, temperature, solvent-to-sample ratio, and pH and yield as response were selected. Inulin was purified using a hot water extraction followed by a slurry of calcium hydroxide and phosphoric acid. TLC-FLD, MALDI-TOF, and spectrophotometric methods were used to characterize and compare the DP of inulin. Results: RSM proposed a maximum yield (10.1 %) at a temperature of 79.6 °C, time of 31.9 min, the solvent-to-sample ratio of 39.9: 1, and pH of 7.7. The quality of extracted inulin was evaluated as follow: FT-IR spectra indicated typical bands at 820, 864, and 932 cm-1 that assigned the presence of 2-ketose, β-(2→1) fructofuranosyl unit, and α-D-glucopyranose residue. Inulin with DP (16) and molecular weight 2633 Da was determined in MALDI-TOF. Furthermore, TLC-FLD confirmed the approximate fructose and DP from (1-15). Also, the spectrophotometric method showed an approximate number of 22.3 ± 0.04 as the DP. Conclusion: In conclusion, the optimized isolation factors for inulin from the Inula helenium were proposed. In comparison with the spectrophotometric result, TLC-FLD quantitative result is much more confirmable to MALDI-TOF. TLC-FLD technique offered a simple and more precise than the spectrophotometric method for the quality of inulin.